2021
DOI: 10.1111/epi.16896
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cognitive outcome after radiosurgery in epileptic hypothalamic hamartomas and review of the literature

Abstract: Objective Epileptic patients with hypothalamic hamartoma (HH) frequently present cognitive impairments. Surgical techniques aiming at HH can be very efficient for epilepsy relief and cognitive improvement but are also demonstrated to carry a significant risk of additional reduction in memory function in these already disabled patients. Gamma knife radiosurgery (GKS) offers an efficient minimally invasive procedure. We evaluated the effect of stereotactic radiosurgery on cognitive outcome. Methods We designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Articles from the same institution as Curry et al 17 that included patients in a similar period were also excluded. 18,19 Studies by Sonoda et al 20 and Hamdi et al 21 were also excluded since they reported cognitive results rather than epilepsy outcomes after HH treatment. Four articles [22][23][24][25] were excluded because of duplicated data with the study by Shirozu et al 26 Only 7 patients from Abla et al 27 and 6 from Mathieu et al 28 were included because other procedures were performed during the follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Articles from the same institution as Curry et al 17 that included patients in a similar period were also excluded. 18,19 Studies by Sonoda et al 20 and Hamdi et al 21 were also excluded since they reported cognitive results rather than epilepsy outcomes after HH treatment. Four articles [22][23][24][25] were excluded because of duplicated data with the study by Shirozu et al 26 Only 7 patients from Abla et al 27 and 6 from Mathieu et al 28 were included because other procedures were performed during the follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Although functional decline in pediatric epilepsy patients after surgery occurs in a minority of patients, some evidence suggests that outcomes beyond a year postoperatively are needed to appreciate the positive impact on cognitive functioning. [28][29][30] Establishing infrastructure for a prospective longitudinal database across centers is essential to rigorously achieving epilepsy benchmarks set forth by the epilepsy field to transform pediatric epilepsy care.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, longitudinal outcomes of the cohort will be most informative in predicting and guiding the optimal timing of surgical treatment in the context of the developmental trajectory of neuropsychological functioning. Although functional decline in pediatric epilepsy patients after surgery occurs in a minority of patients, some evidence suggests that outcomes beyond a year post‐operatively are needed to appreciate the positive impact on cognitive functioning 28–30 . Establishing infrastructure for a prospective longitudinal database across centers is essential to rigorously achieving epilepsy benchmarks set forth by the epilepsy field to transform pediatric epilepsy care.…”
Section: Discussionmentioning
confidence: 99%
“…The risks and adverse events might outweigh the clinical benefits in many cases since it is associated with severe memory disorders especially when used to treat MTLE. However, a literature review published in the Epilepsia Journal showed promising long-term cognitive outcome after the treatment of epileptic hypothalamic hamartomas using this method [55].…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%